Search for the Standard Model Higgs boson in the H -> tau(+)tau(-) decay mode in root s=7 TeV pp collisions with ATLAS - Onofre, A. (2012)
A search for the Standard Model Higgs boson decaying into a pair of τ leptons is reported. The analysis is based on a data sample of proton-proton collisions collected by the ATLAS experiment at the LHC and corresponding to an integrated luminosity of 4.7 fb−1. No significant excess over the expected background is observed in the Higgs boson mass range of 100–150 GeV. The observed (expected) upper limits on the cross section times the branching ratio for H → τ+τ− are found to be between 2.9 (3.4) and 11.7 (8.2) times the Standard Model prediction for this mass range.